1997
DOI: 10.1007/bf02303794
|View full text |Cite
|
Sign up to set email alerts
|

Repeat hepatic resection as effective treatment for recurrent colorectal liver metastases

Abstract: Repeat liver resection for recurrent colorectal metastases (a) can be performed safely with acceptable mortality and morbidity rates and (b) may result in long-term survival in some patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0
4

Year Published

2000
2000
2007
2007

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(52 citation statements)
references
References 27 publications
2
46
0
4
Order By: Relevance
“…Many studies have documented favorable long-term survival in highly selected patients undergoing second resection for recurrent colorectal liver metastases, with 5-year survival rates of up to 41%. [21][22][23][24] In summary, these data provide further support for longterm benefit of liver resection of hepatic colorectal metastases. Based on our experience, overall and disease-free survival is improving over time.…”
Section: Discussionmentioning
confidence: 73%
“…Many studies have documented favorable long-term survival in highly selected patients undergoing second resection for recurrent colorectal liver metastases, with 5-year survival rates of up to 41%. [21][22][23][24] In summary, these data provide further support for longterm benefit of liver resection of hepatic colorectal metastases. Based on our experience, overall and disease-free survival is improving over time.…”
Section: Discussionmentioning
confidence: 73%
“…All efforts should be made to eliminate the hepatic lesions after controlling the loco-regional disease and ruling out extrahepatic tumor spread. In such cases there are well documented reports demonstrating a 5-year survival of 20%-40% [1][2][3][4][5][6] , and 20%-30% when a re-resection has been executed in highly selected individuals [6][7][8][9] . The indications and criteria of patient selection for liver surgery due to metachronous colorectal metastases have been clarified in numerous excellent papers [14][15][16] .…”
Section: Discussionmentioning
confidence: 99%
“…Even re-resections of liver metastases are rewarded with a 5 year-survival of 20%-30% and should be carried out in selected patients [6][7][8][9] . Many aspects of surgical strategies for the management of colorectal liver metastases have been extensively analyzed [10][11][12][13][14][15] and patient selection has been elucidated [1,3,7,[15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…The presence of recurrent liver metastases was historically considered to have a poor prognosis and routine screening for patients having undergone resection of colorectal liver metastases was felt not to be justified by analysis of cost to benefit ratio (Biggs and Ballantyne, 1994;Beard et al, 2000). However, recent studies have shown a 35 -40% survival at 5 years following surgery for recurrent liver metastases (Tuttle et al, 1997;Yamamoto et al, 1999a;Muratore et al, 2001;Suzuki et al, 2001;Yamada et al, 2001a). These results reflect a better outcome with a more aggressive approach towards the treatment of colorectal liver metastases and careful follow-upof patients following resection of the liver metastases is therefore essential.…”
mentioning
confidence: 99%